Virulence and molecular genetic diversity, variation, and evolution of the Puccinia triticina population in Hebei Province of China from 2001 to 2010 - Zhang, Lin; Zhang, Linya; Meng, Qingfang; Yan, Hongfei; Liu, Daqun (Frontiers in Plant Science, 2023)
Wheat leaf rust, caused by Puccinia triticina, is one of the most important fungal diseases of wheat in China. In this study, 247 isolates of P. triticina collected from Hebei Province from 2001 to 2010 were tested on 36 Thatcher near-isogenic lines for the virulence diversity and detected by 21 pairs of EST-SSR primers for genetic diversity. A total of 204 isolates were successfully identified as 164 races, and THTT, THST, PHRT, THTS, and PHTT were the most common races in Hebei Province from 2001 to 2010. The cluster analysis based on virulence showed that P. triticina has rich virulence polymorphism, which had a certain correlation with the years, while the cluster analysis based on EST-SSR showed that the genetic diversity of P. triticina population was significantly different between years in Hebei Province from 2001-2010. In addition, the population structure of P. triticina may have changed greatly in 2007 and 2009, which were significantly different from 2001-2006 either on virulence or genetic characteristics. The variation frequency of population structure had an increasing trend during this period. From 2001 to 2010, there was a certain degree of gene flow among P. triticina population. No significant correlation was found between virulence and molecular polymorphism. The genetic differentiation analysis of 10 tested populations (each year as a population) showed that the coefficient of genetic differentiation (Gst) was 0.27, indicating there was a certain genetic differentiation among or within populations of P. triticina in Hebei Province. The genetic variation within populations (73.08%) was higher than that among populations (26.92%). Our study provides the foundation for a better understanding of the population structure change and genetic diversity of P. triticina over a period in Hebei Province of China.